-4= -4x to the third power - 4x to the second power.
![4 4x to the third power 4x to the second power class=](https://us-static.z-dn.net/files/d82/6588994b864c12c6a01b1794bab024b0.png)
Answer:
-16
Step-by-step explanation:-4=-4x to the power of 3,-4 to the power 2
=-4=4x to the power of 3
=-64 -4 to the power of 2
=-16
Answer:
x = 0.754878...
Step-by-step explanation:
Hi there! I'm glad I was able to help you solve this math problem!
First, you'll want to subtract -4x^3 - 4x^2 from each side of the equation. This cancels out the right side of the problem, leaving us with a problem that equals zero.
-4 - (-4x^3 - 4x^2) = -4x^3 - 4x^2 - (-4x^3 - 4x^2)
4x^3 + 4x^2 - 4 = 0
Next, we use the cubic formula to solve for x. You can use a calculator to do this part for you!
x = 0.754878... is your answer.
I hope this helped you! Leave a comment below if you have any other questions! :)